2000
DOI: 10.1007/s004050050206
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus in cholesteatomas

Abstract: The presence of human papillomavirus DNA in cholesteatoma may have some role in the development of middle ear cholesteatoma as well as in papilloma. In the present study, polymerase chain reaction and in situ hybridization with human papillomavirus (HPV)-6 and -11 DNA probes were used to detect the presence of HPV DNA in 32 human middle ear cholesteatomas. Only one specimen contained HPV-6 DNA. Although its occurrence may have been coincidental, it is also possible that the hyperproliferative epithelium of cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…The present study and the earlier results of Chao et al [11] both show a low prevalence of HPV DNA in cholesteatomas. Based on these results, an aetiological role of HPVs in the pathogenesis of cholesteatomas is unlikely, even if the histopathological appearance of a cholesteatoma exhibits features of HPV-induced lesions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The present study and the earlier results of Chao et al [11] both show a low prevalence of HPV DNA in cholesteatomas. Based on these results, an aetiological role of HPVs in the pathogenesis of cholesteatomas is unlikely, even if the histopathological appearance of a cholesteatoma exhibits features of HPV-induced lesions.…”
Section: Discussionsupporting
confidence: 62%
“…Based on the results of these two studies, Chao et al [11] focused on the detection of HPV-6 and -11 DNA in cholesteatomas. They applied PCR and in situ hybridization with an HPV-6-or HPV-11-specific probe, claiming a sensitivity of 0.1 viral copy/cell.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic migration of ectodermal tissue to the middle ear may also be implied in the genesis of this pathology 4,5 . Chao et al 6 showed association between HPV and cholesteatoma and middle ear papilloma without defining a causal correlation. However, Xia et al 1 demonstrated a dissemination of the squamous papilloma of nasopharynx to the tympanic membrane through the performance of myringotomy concomitantly with papilloma surgical treatment in the nasopharynx, indicating the likely infectious nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…There is great interest in the etiopathogenesis of HPV-associated cholesteatoma because HPV commonly infects the stratified epithelium [17,18]. However, conflicting data have been reported for HPV in COMC [10,[19][20][21]. HPV sequences have been detected in COMC with different prevalence, ranging from 3% to 70% [10,[19][20][21].…”
mentioning
confidence: 99%
“…However, conflicting data have been reported for HPV in COMC [10,[19][20][21]. HPV sequences have been detected in COMC with different prevalence, ranging from 3% to 70% [10,[19][20][21]. Moreover, no specific HPV genotypes have been associated with COMC, as high-and low-risk HPVs, such as HPV16, HPV18 and HPV6 and HPV11, have been detected [10,[19][20][21].There is emerging evidence that HPV infection can occur in different anatomical sites.…”
mentioning
confidence: 99%